2021
DOI: 10.1039/d1sc01024g
|View full text |Cite
|
Sign up to set email alerts
|

A donor–acceptor complex enables the synthesis of E-olefins from alcohols, amines and carboxylic acids

Abstract: Olefins are prevalent substrates and functionalities. The synthesis of olefins from readily available starting materials such as alcohols, amines and carboxylic acids is of great significance to address the sustainability...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 68 publications
2
24
0
1
Order By: Relevance
“…Furthermore, their conversion to Katritzky pyridinium salts ( 1 ) makes them competent precursors to alkyl radical intermediates . Since our 2017 report, these Katritzky pyridinium salts have been activated via single-electron transfer (SET) using nickel catalysts or stoichiometric reductants (e.g., Mn), , photoredox catalysis, and photochemically promoted electron transfer of electron donor–acceptor (EDA) complexes. , Rare examples of thermally promoted SET of EDA complexes of alkylpyridinium salts with amine bases have also been reported . In developing this reaction, we have discovered the ability of potassium carbonate to form a complex with the alkylpyridinium salt, which undergoes SET under thermal conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, their conversion to Katritzky pyridinium salts ( 1 ) makes them competent precursors to alkyl radical intermediates . Since our 2017 report, these Katritzky pyridinium salts have been activated via single-electron transfer (SET) using nickel catalysts or stoichiometric reductants (e.g., Mn), , photoredox catalysis, and photochemically promoted electron transfer of electron donor–acceptor (EDA) complexes. , Rare examples of thermally promoted SET of EDA complexes of alkylpyridinium salts with amine bases have also been reported . In developing this reaction, we have discovered the ability of potassium carbonate to form a complex with the alkylpyridinium salt, which undergoes SET under thermal conditions.…”
mentioning
confidence: 99%
“…However, a control experiment demonstrated that this reaction proceeds in increased yield without photocatalyst (48%, entry 2). We hypothesized this reaction to be occurring via activation of the alkylpyridinium salt within an electron donor–acceptor (EDA) complex. , Surprisingly, the yield was not impacted when this reaction was performed in the dark at 50 °C (entry 3). We also observed a strong effect of the equivalents and solubility of the carbonate base (entries 3–5) and on the identity of the base (entries 6–8).…”
mentioning
confidence: 99%
“…A deaminative alkyl-Heck-type reaction via an Ir-based photocatalyst has also been reported by Xiao, Lu, and co-workers . Very recently, we found that the weak interaction of Katritzky salts and NaI enabled the formation of a photoactive electron donor–acceptor (EDA) complex for the functionalization of alkenes . Encouraged by these developments and the solvent effect on the EDA complex, we examined the possibility of an EDA-complex-enabled cascade radical cyclization of N -arylacrylamides with Katritzky salts without any additives for the synthesis of 3-alkyl-3-substituted oxindoles (Scheme D).…”
mentioning
confidence: 69%
“…Alternatively, radical−radical cross-coupling with an iodine radical or the direct abstraction of a bromine atom from substrate 1 resulted in the intermediate 6. Finally, the 5,9 which would proceed in a S N 2′-type reaction to ultimately give the product 3.…”
mentioning
confidence: 99%
“…Finally, the intermediate 6 underwent a nucleophilic substitution and the subsequent elimination of HF promoted by the base to deliver the intermediate B . Otherwise, the intermediate 6 underwent an elimination process to generate intermediate 7 , , which would proceed in a S N 2′-type reaction to ultimately give the product 3.…”
mentioning
confidence: 99%